Priester-dichter Jan-Mathijs Winters 1864-1935 - Remans, A. (Genk : s.n., 1964)
Bibliotheek Camille Huysmans
Dedicator: Remans, A., dedicatee: Huysmans, Camille
Nederlands
Monografie
Keywords: poëzie; Limburg